Crash analysis of an aircraft fuselage under belly landing - Syed Mohamed Ali, Jaffar; M.Y., Hasfareeza (Institute of Institutional Industrial Research (IIIR), 2017)
Belly landing occurs when an aircraft lands without deploying its landing gear due to pilot error or mechanical failure. In the present work crash analysis of the fuselage under such belly landing is studied by numerical simulation using LS-DYNA software. In this study both the effect of sinking speed and the effect of different terrain properties on energy absorbing capacity is considered. Fuselage structure was modelled using LS-DYNA to simulate the crash analysis of the fuselage under vertical drop. The fuselage section similar to Boeing 737 aircraft was dropped at 7m/s and 10m/s on a rigid surface as well as on water and the deformations of fuselage were noted for each case and the energy absorbed by each of the components of the fuselage was evaluated. From the result obtained, it shows that frame and skin plays important roles in absorbing energy under crash.